2021
DOI: 10.3389/fvets.2021.752001
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Promotes in vitro Development of Vitrified-Warmed Mouse GV Oocytes, Potentially by Modulating Phosphorylation of Drp1

Abstract: Previous studies have shown that melatonin can mitigate cryopreservation-induced mitochondrial dysfunction in oocytes; however, the underlying molecular mechanism remains unclear. The objective of the present study was to investigate whether melatonin can improve the mitochondrial function during in vitro maturation of vitrified-warmed mouse germinal vesicle (GV) oocytes by modulating phosphorylation of dynamin related protein 1 (Drp1). Vitrification/warming procedures resulted in the following: (1) After cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…In our experiments, we found that the expression of DRP1 and Fis1 expression was reduced in mice ovaries after CP treatment, which was consistent with previous studies that CP exerts its adverse effects on the human ovarian cancer SKOV3 cells through mitochondrial dynamics-related proteins [26]. Moreover, DRP1-mediated mitochondrial dynamics were involved in the effect of CP on acute kidney injury [27]. Our study also revealed that the new kinetic-related protein Fis1 was involved in the action of CP on the ovary.…”
Section: Discussionsupporting
confidence: 91%
“…In our experiments, we found that the expression of DRP1 and Fis1 expression was reduced in mice ovaries after CP treatment, which was consistent with previous studies that CP exerts its adverse effects on the human ovarian cancer SKOV3 cells through mitochondrial dynamics-related proteins [26]. Moreover, DRP1-mediated mitochondrial dynamics were involved in the effect of CP on acute kidney injury [27]. Our study also revealed that the new kinetic-related protein Fis1 was involved in the action of CP on the ovary.…”
Section: Discussionsupporting
confidence: 91%
“…Current research also investigated the mechanism by which oxidative stress adversely affected the embryo development. Previous studies suggested that mitochondrial dysfunction induced by oocyte vitrification exacerbated ROS production [ 21 , 68 ]. The excessive ROS in turn inhibited the activity of glycolytic pyruvate kinase M2 (PKM2) by promoting its phosphorylation, which consequently reduced the production of the glycolytic products like lactate [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 10 −7 mol/L melatonin can improve spindle morphology through MTRs, regulate the levels of MAD2 protein, an important component of the SAC, and subsequently improve the in vitro developmental potential of vitrified-warmed mouse GV-stage oocytes [ 88 ]. In addition, oocyte cryopreservation can lead to increased phosphorylation levels of kinesin-related protein 1 (Drp1), while 10 −7 mol/L melatonin was able maintain mitochondrial fission/fusion homeostasis via MTRs that reduce Drp1 phosphorylation levels, protecting mitochondrial function, reducing the release of pro-apoptotic genes and cytochrome C, and improving the survival rate of vitrified-warmed mouse GV-stage oocytes [ 130 ].…”
Section: Mechanism Of Exogenous Non-enzymatic Antioxidants and Their ...mentioning
confidence: 99%